Ethnic-Cultural Identities of Kazan Residents. Issue 1 (2nd January 2019) - Makarova, Guzel I.
Abstract : The multiplicity of ethnic and cultural identities of residents of large cities derives from a series of factors. Of particular significance is whether they come from a rural or urban locale, the focus of the article is interviews conducted with families of Kazan residents who self-identify as Tatars and Russians who have revealed substantive differences in the intensity and content of their associations with their "own" ethnic group. They vary in language practices, in knowledge and observance of traditional rites and holidays, and in how ethnic identities are manifest in cultural preferences and in mapping ethnic-cultural boundaries of the featured groups. At the same time, interview transcripts have revealed attitudes, values, and cultural preferences that appear shared by the majority of Kazan residents, both Russian and Tatar.